Comment la crise énergétique reconfigure les débats sur la sobriété. Une analyse des problématisations dans la presse nationale française - Alexandre Mallard (VertigO, 2025)
This article studies the debates in the French national press around the notion of energy sufficiency over the last 15 years. Based on an analysis using the CorText tool, it follows the way in which the notion of sufficiency was the subject of successive problematizations during the period 2009-2021, and it examines the transformations that took place with the energy crisis of 2022. It thus highlights the forms of politicization which are deployed around the surge in energy prices and the risks of disruptions in energy supplies, as well as the forms of government of sufficiency deployed in 2022. It finally questions the figures of sufficiency as an object of political and moral discussion or as a component of the trajectories of innovations for energy and climate as they appear in the press.